Analysis of the performance test results of young pure breed boars from the Bydgoszcz breeding region in Poland - Grażyna MICHALSKA; Jerzy NOWACHOWICZ; Tomasz BUCEK; Przemysław WASILEWSKI (Journal of Central European Agriculture, 2016)
The aim of presented paper was analysis of the performance test results of young pure breed boars coming from The Bydgoszcz Breeding Region (located in Poland in Kujawy-Pomorze Province). The research covered the results concerning 4190 young boars of following breeds: Polish Large White, Polish Landrace, Hampshire, Duroc and Pietrain. Young pure breed boars were performance tested in 2009 and 2010 in The Bydgoszcz Breeding Region according to the actual methodology. Among young pure breed boars performance tested in The Bydgoszcz Breeding Region in tested years animals of Hampshire breed had the higher growth rate. The pigs of Pietrain breed had the highest meat content. Regarding to the most important parameter of performance test, i.e. selection index in analyzed years 2009 and 2010 the best results had young boars of Hampshire then Pietrain, Duroc, PLW and PL.